Pengaruh Celebrity Endorsment, Online Review Customer dan Promo Gratis Ongkir terhadap Minat Beli Produk Shopee - Widhianingrum, Galuh; Octavia, Ayu Nurafni (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
Shopee visitor fluctuations occur due to several factors. This is thought to be due to declining consumer interest. This condition makes Shopee have to think about how to increase purchasing interest so that it can increase. The aim of this research is to determine the influence of celebrity endorsements, online customer reviews and free shipping promotions on purchasing interest. The research method used is quantitative with multiple linear regression analysis. The population consists of residents of Grobogan Regency. The research sample consisted of 100 respondents selected using purposive sampling technique. The tool used is SPSS 25 and the tests carried out include validity tests, reliability tests, classical assumption tests which include normality tests, heteroscedasticity tests and multicollinearity tests. To test the hypothesis, the t test and f test are used, the last is the coefficient of determination test. The results of this research show that partially, celebrity endorsement (X1) has no effect on buying interest (Y), while online customer reviews (X2) have an effect on buying interest (Y) and free shipping promos (X3) have an effect on buying interest (Y). . Simultaneously, celebrity endorsements, online customer reviews and free shipping promotions have a joint effect on purchasing interest. Based on the coefficient of determination test, the R Square value of 0.498 shows that the variables celebrity endorsement, online customer reviews and free shipping promos can influence Shopee consumers' buying interest by 49.8% and the remaining 50.2% is influenced by other variables not examined in this research